Pengaruh Kualitas SDM dan Motivasi Terhadap Produktivitas Kerja Karyawan Bagian Produksi PT. Kerta Rajasa Raya - Hilmi Putra, Muhammad; Sri Umiyati; Setya Prihatiningtyas (Journal Of Accounting and Business, 2023)
This study aims to determine and examine the effect of HR quality (X₁) and Motivation (X₂) on Employee Productivity (Y) in the production division of PT. Kerta Rajasa Raya by using the type of research asositif using quantitative method by using a casual relationship approach. The total population of the study was 190 with a total sample of 66 production employees using multiple linear regression analysis techniques. The results of the analysis of this study prove partially (t test) the variable HR Quality (X₁) by obtaining a significant value of 0.005 <0.05 and tcount (-2.889) > ttable (1.999) which has a negative effect or opposite direction and is significant, while the variable Motivation (X₂) by obtaining a significant value of 0.001 <0.05 and tcount (3.540) > ttable (1.999) which is a positive or unidirectional and significant effect. And simultaneously (Test F) by obtaining a significant value of 0.000 <0.05 while the value of Fcount 10.102 > Ftable 2.751 means that it has an effect and is significant on Employee Productivity.